Implementasi Kebijakan Penanggulangan Kemiskinan Masyarakat Pesisir Kecamatan Seunuddon (Studi Pada Dinas Kelautan Dan Perikanan Kabupaten Aceh Utara) - Taufik Gunawan; Muhaddis Muhaddis; Ana Zahara; Amru Alba (Universitas 17 Agustus 1945, 2023)
The Government of Aceh in 2013 issued Aceh Qanun Number 11 of 2013 concerning Social Welfare. North Aceh Regency to overcome this has carried out a variety of policies / programs with the aim of finding solutions in terms of poverty alleviation of coastal communities, but not yet optimal, the number of poverty continues to increase and and decrease from year to year, we can see that the Aceh District Government The North does not seem to be serious in suppressing and overcoming poverty, based on the writer's findings that there are still many of the coastal poverty alleviation programs that are not yet right on targeting the people who are the object of the policy / program. The purpose of this research is to analyze and describe the implementation of poverty reduction policies in coastal communities in Seunuddon District. To describe the constraints of the government in poverty alleviation of coastal communities. The study uses a qualitative approach to the type of descriptive analysis research. The results showed that the implementation of policies in poverty reduction in coastal communities in Seunuddon District the government worked with the North Aceh Regional Planning and Development Agency (BAPPEDA), North Aceh Central Statistics Agency (BPS), the Fisheries and Maritime Affairs Office, and the Social Service. The Department of Fisheries and Maritime Affairs has implemented and provided socialization to the community regarding poverty alleviation programs for the poor coastal communities, in general the poverty of coastal communities in the District of Seunuddon is influenced by cultural and structural factors. The obstacle of the government in reducing poverty of coastal communities in Seunuddon District, is related to the lack of budget, resources, facilities and infrastructure, as well as very limited information.